Program Corporate Social Responsibility Humas Rumah Sakit Islam Jakarta Pondok Kopi bagi Masyarakat - Lisna Fitriani; Fajar Diah Astuti (Jurnal Public Relations (J-PR), 2021)
Corporate Social Responsibility (CSR) is a communication activity that is considered important and should be considered by each company. This is because one of the tasks of Public Relations (PR) is as an instrument to be responsible for all groups entitled to these responsibilities. Especially the internal public groups and the external public, especially the surrounding community. Public relations as a mediator and communicator in an organization/institution includes one of which is fostering good relations with the external public. This is very closely related to the role and duties of a public relations officer to create a positive image for his agency. Pondok Kopi Jakarta Islamic Hospital is one of the hospital agencies that are aware of this. For this reason, Pondok Kopi Islamic Hospital Rumas carried out CSR activities with the theme of Social Service for the Bekasi Flood Disaster, where the targets were several areas that were subscribed to floods in Bekasi. This research uses observation research methods, interviews with several sources, literature studies and documentation obtained from various sources. While the data analysis method used is descriptive qualitative.